Development of a RP-HPLC Method for Separating and Quantifying Muscimol in Different Developmental Stages of the Fungus Amanita muscaria - Emersón León Ávila; James Guevara-Pulido (Journal of Chemistry)
A simple RP-HPLC method was designed for the quantification of muscimol (5-(aminomethyl)-isoxazol-3-ol) present in five aqueous extracts of Amanita muscaria each from a different developmental stage. Results show that the maximum concentration of muscimol (1,210 mg/ml) was found in the young mushroom stage of development. Moreover, it was also found that this concentration progressively decreases as the fungus ages. The developed method is a simple but effective method for the quantification of muscimol, a widely important metabolite for the pharmaceutical industry as a possible treatment for tardive dyskinesia and Parkinson’s disease.